Health behavior of nursing students - Walentukiewicz, Anna; Łysak, Anna; Wilk, Barbara (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Issues of health behaviour are topical items in Poland at the moment. They concentrate around all health oriented activities of different groups of population. Aim. The purpose of the research was the assessment of health behaviours in women students of Nursing. Material and methods. The findings of the research on the first year women students of Nursing were analysed. Diagnostic survey was carried out in the academic year 2010/2011. A questionnaire as a research tool consisted of 3 parts relating to: health behaviours, nutrition and the level of physical activity. The assessment of health behaviours was based on the Set of Health Behaviours. Body mass values were evaluated with reference to BMI. The level of physical activity was assessed by the IPAQ. Results. General intensity of health behaviours for the examined group amounted to 73.19, what according to the standard ten equals sten 4 and is interpreted as a low result. Analysing individual categories of health behaviours, positive psychological attitudes were highly assessed, whereas practical health behaviours ranked the lowest. None of the subjects had received a high level of physical activity. Physical activity level considered as sufficient achieved only 42% of the whole subjects. Conclusions. Low level of health behaviours in women students of Nursing suggests the need for drawing attention to that particular group in further research. Medical school students should be an authority in the field of health behaviors and promote such behaviours among patients as arising from their own individual conviction and attitudes towards health.